Carbene in cupredoxin protein scaffolds: replacement of a histidine ligand in the active site substantially alters copper redox properties - Planchestainer, Matteo; Segaud, Nathalie; Shanmugam, Muralidharan; McMaster, Jonathan; Paradisi, Francesca; Albrecht, Martin (Wiley-VCH Verlag, 2018)
N-heterocyclic carbene (NHC) ligands have had a major impact in homogeneous catalysis, however, their potential role in biological systems is essentially unexplored. Here we replaced a copper-coordinating histidine (His) in the active site of azurin with exogenous dimethyl-imidazolylidene; this NHC rapidly restores the type-1 Cu center with spectroscopic properties (EPR, UV-vis) that are identical to those from N-coordination of the His in the wild type. However, the introduction of the NHC markedly alters the redox potential of the metal, key functionality of this blue copper protein. These results suggest that C-bonding for histidine is plausible and a potentially relevant bonding mode of redox-active metalloenzymes in their (transient) active states.